Total antioxidant status in lung cancer is associated with levels of endogenous antioxidants and disease stage rather than lifestyle factors – preliminary study - Zabłocka-Słowińska, Katarzyna; Porębska, Irena; Gołecki, Marcin; Kosacka, Monika; Pawełczyk, Konrad; Pawlik-Sobecka, Lilla; Zarębska, Katarzyna; Grajeta, Halina (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Decreased total antioxidant capacity (TAC) has been reported in different neoplasms, including lung cancer. However, no study concerning the relationship between endogenous antioxidants, lifestyle factors, and TAC has been conducted among lung cancer patients. The purpose of the study was to investigate the associations between endogenous antioxidants, severity of disease, lifestyle factors, and TAC in lung cancer patients. Material and methods : The study was conducted among 59 lung cancer patients. The levels of total antioxidant status (ATBS method), endogenous antioxidants, and C-reactive protein were measured in patients’ sera automatically. Dietary habits of the subjects were evaluated based on the Food Frequency Questionnaire (FFQ) on the day of admission to hospital. Results: We found a positive correlation between serum albumin, uric acid (UA), and TAC and a negative correlation between CRP and TAC. Moreover, TAC was significantly positively associated with disease stage. We did not find any significant relationship between the frequency of selected food consumption and TAC in lung cancer patients, except for a positive correlation between the frequency of refined cereal products consumption and TAC level. Smoking status did not correlate with TAC. Conclusions : Total antioxidant status of lung cancer patients results from their disease stage and levels of endogenous antioxidants rather than from lifestyle factors. The lack of influence of diet and smoking on the TAC presumably result from disturbed homeostasis in which cancer, while developing, could determine the redox state to a greater extent than lifestyle factors.